2006
DOI: 10.1007/s11258-006-9161-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenological patterns of Ficus citrifolia (Moraceae) in a seasonal humid-subtropical region in Southern Brazil

Abstract: Year-round flowering is widely reported in fig trees and is necessary for the survival of their short-living, specialized Agaonid pollinators. However, seasonality in both fig and leaf production has been noted in almost all published phenological studies. We have addressed the following questions in the present study: (1) Are reproductive and vegetative phenologies seasonal and, consequently, related to climate? (2) Does Ficus citrifolia produce ripe figs year round? (3) Is the fig development related to clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 49 publications
2
22
1
9
Order By: Relevance
“…In spite of this phenophase occur throughout the year, we observed periods of higher syconia production in F. adhatodifolia, as previously reported in other studies on Ficus (Milton et al, 1982;Windsor et al, 1989;Lambert and Marshall, 1991;Spencer et al, 1996;Ragusa-Netto, 2002;Pereira et al, 2007). The population asynchrony would be required for maintenance of the pollinating wasps population (Smith and Bronstein, 1996) while periods of increased production could be related to best time for dispersal and/or seed germination (Milton et al, 1982).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In spite of this phenophase occur throughout the year, we observed periods of higher syconia production in F. adhatodifolia, as previously reported in other studies on Ficus (Milton et al, 1982;Windsor et al, 1989;Lambert and Marshall, 1991;Spencer et al, 1996;Ragusa-Netto, 2002;Pereira et al, 2007). The population asynchrony would be required for maintenance of the pollinating wasps population (Smith and Bronstein, 1996) while periods of increased production could be related to best time for dispersal and/or seed germination (Milton et al, 1982).…”
Section: Discussionsupporting
confidence: 83%
“…Miq.). Ficus citrifolia (subgenus Urostigma) was also considered deciduous (Pereira et al, 2007) in the same region of this study. These variation in leaf dynamics may possibly reflect different adaptations to water deficits in hemi-epiphytic and freestanding species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synchronicity in the foliar exchange of F. thonningii, F. citrifolia (Damstra et al, 1996) and F. variegata (Spencer et al, 1996) was interpreted, based on estimations of water status through rainfall values, as due to water deficit during the dry season. In contrast, Pereira et al (2007) concluded that measured rainfall and estimated soil water storage probably did not accurately reflect the actual water status of trees of F. citrifolia, in which no relationship was found between the abovementioned variables and leaf exchange.…”
Section: Introductionmentioning
confidence: 93%